171k views
1 vote
What is the third term in sequence a(n)=3/2(-2)n-1

User Hare Kumar
by
5.4k points

2 Answers

5 votes

Answer:

-10

Explanation:

First, you know n=3, so you plug that in. Then that equals A(n) = 3/2(-2)3-1, which can be simplified into 3/2*-6-1, then -9-1, and finally -10. [I did the 3/2*-6 by first: multiply -6*3=-18, then -18/2=-9.]

Hope this helps!

User Linepogl
by
6.0k points
4 votes

We have the general term of a sequence:


a_n=(3)/(2)(-2)^(n-1)

We must find the third term. Therefore substitute n = 3 to the equation:


a_3=(3)/(2)(-2)^(3-1)=(3)/(2)(-2)^2=(3)/(2)(4)=3(2)=6

Answer: The third term is equal 6.

User Luixal
by
6.1k points